Networked Influence in Social Media: Introduction to the Special Issue. (September 2014) - Gruzd, Anatoliy; Wellman, Barry
This special issue presents leading-edge work into how the characteristics of social media affect the nature of influence in networks. Our central thesis is that social influence has become networked influence. Influence is networked in two ways: by occurring in social networks and by propagating through online communication networks. We want to understand online social influence in its diversity: who is exercising influence, how it is done, how to measure influence, what its consequences are, and how online and offline influences intertwine in different contexts.